Mycobiome diversity: high-throughput sequencing and identification of fungi - Nilsson, R Henrik; Anslan, Sten; Bahram, Mohammad; Wurzbacher, Christian; Baldrian, Petr; Tedersoo, Leho (Nature reviews. Microbiology, 2019)
Fungi are major ecological players in both terrestrial and aquatic environments by cycling organic matter and channelling nutrients across trophic levels. High-throughput sequencing (HTS) studies of fungal communities are redrawing the map of the fungal kingdom by hinting at its enormous - and largely uncharted - taxonomic and functional diversity. However, HTS approaches come with a range of pitfalls and potential biases, cautioning against unwary application and interpretation of HTS technologies and results. In this Review, we provide an overview and practical recommendations for aspects of HTS studies ranging from sampling and laboratory practices to data processing and analysis. We also discuss upcoming trends and techniques in the field and summarize recent and noteworthy results from HTS studies targeting fungal communities and guilds. Our Review highlights the need for reproducibility and public data availability in the study of fungal communities. If the associated challenges and conceptual barriers are overcome, HTS offers immense possibilities in mycology and elsewhere.
Keywords: houby; vysoce účinné nukleotidové sekvenování; Biodiversity; Reproducibility of Results; mykobiom; Mycobiome; DNA Barcoding, Taxonomic; reprodukovatelnost výsledků; Fungi; High-Throughput Nucleotide Sequencing; taxonomické DNA čárové kódování; biodiverzita